MIXED CULTURE CYTOPATHOGENICITY: A NEW TEST FOR GROWTH OF MURINE LEUKEMIA VIRUSES IN TISSUE CULTURE - Klement, Vaclav (1969)
Tissue culture cells of a Rous virus-induced rat tumor undergo syncytium formation when placed in contact with mouse embryo cell cultures infected with murine leukemia viruses. This phenomenon can be used as a cytopathic end point for isolating and titrating these viruses in tissue culture. The principle should be applicable to detection of leukemia viruses of other species.